Consumer Habituation - Wathieu, Luc (Management Science, 2004)
This paper examines how consumers’ willingness to pay for goods is determined by past patterns of consumption. The central result is a theorem of interior maximum, which states that willingness to pay for a good is maximized at a moderate level of habitual consumption. The theorem is derived from a simple model of adaptive behavior that involves a shifting S-shaped value function. The detailed analysis of the impact of consumption frequency and intensity on willingness to pay reveals an unsuspected implication of diminishing sensitivity, even as it leads to a formalization of consumer habituation patterns (including sensitization, habituation, and response recovery upon withdrawal) that matches and integrates the most robust empirical regularities attendant on nonassociative learning in neurobiology and behavioral psychology. An examination of the implications for demand dynamics and pricing highlights deterministic recurrent and transient patterns of consumption at higher price points.